2010
DOI: 10.1128/aac.00254-10
|View full text |Cite
|
Sign up to set email alerts
|

Actinohivin, a Broadly Neutralizing Prokaryotic Lectin, Inhibits HIV-1 Infection by Specifically Targeting High-Mannose-Type Glycans on the gp120 Envelope

Abstract: The lectin actinohivin (AH) is a monomeric carbohydrate-binding agent (CBA) with three carbohydratebinding sites. AH strongly interacts with gp120 derived from different X4 and R5 human immunodeficiency virus (HIV) strains, simian immunodeficiency virus (SIV) gp130, and HIV type 1 (HIV-1) gp41 with affinity constants (K D ) in the lower nM range. The gp120 and gp41 binding of AH is selectively reversed by (␣1,2-mannose) 3 oligosaccharide but not by ␣1,3/␣1,6-mannose-or GlcNAc-based oligosaccharides. AH binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 48 publications
1
52
0
Order By: Relevance
“…This unique structure may bring about its highly specific HMTG binding. Furthermore, AH does not exhibit any mitogenic activity (Hoorelbeke et al, 2010;Matoba et al, 2010) in contrast to the other lectins, e.g. CN-V. As shown in Fig.…”
Section: Figurementioning
confidence: 71%
“…This unique structure may bring about its highly specific HMTG binding. Furthermore, AH does not exhibit any mitogenic activity (Hoorelbeke et al, 2010;Matoba et al, 2010) in contrast to the other lectins, e.g. CN-V. As shown in Fig.…”
Section: Figurementioning
confidence: 71%
“…9 For actinohivin, a broadly neutralizing prokaryotic lectin, a tight interaction with the envelope protein of SIV was demonstrated by surface plasmon resonance technology, but it lacked anti-SIV activity in several viral replication assays. 40 These data revealed that binding of CBAs to gp120 glycans may occur, but these are not always necessarily in neutralizing viral replication. …”
Section: Discussionmentioning
confidence: 99%
“…PRM-S also inhibited dose-dependently DENV-2 replication in MDDC but had only a weak antiviral activity in Raji/DC-SIGN + cells [61]. Actinohivin (AH), a small prokaryotic peptidic lectin containing 114 amino acids, exhibits also anti-HIV-1 activity by recognizing high-mannose-type glycans on the viral envelope [92]. Although DENV has high mannose-type glycans on the E-protein, there was no antiviral activity of AH against DENV infection.…”
Section: Broad Antiviral Activity Of Cbas Against Denvmentioning
confidence: 99%